2015
DOI: 10.2196/jmir.4126
|View full text |Cite
|
Sign up to set email alerts
|

Access to Care and Use of the Internet to Search for Health Information: Results From the US National Health Interview Survey

Abstract: BackgroundThe insurance mandate of the Affordable Care Act has increased the number of people with health coverage in the United States. There is speculation that this increase in the number of insured could make accessing health care services more difficult. Those who are unable to access care in a timely manner may use the Internet to search for information needed to answer their health questions.ObjectiveThe aim was to determine whether difficulty accessing health care services for reasons unrelated to insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
173
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(191 citation statements)
references
References 28 publications
5
173
1
3
Order By: Relevance
“…51 Data from 2011 National Health Interview Survey reported that Whites were more likely to use the Internet to search for health information compared with other races/ethnicities and the percentage of adults who search for health information increased with education level. 52 The promise of Big Data may be offset by challenges that threaten to widen health disparities. Moreover, persons with a more disadvantaged status are particularly vulnerable to unintended adverse effects of information system transformations.…”
Section: Potential Challenges Of Using Big Data For Minority Health Amentioning
confidence: 99%
“…51 Data from 2011 National Health Interview Survey reported that Whites were more likely to use the Internet to search for health information compared with other races/ethnicities and the percentage of adults who search for health information increased with education level. 52 The promise of Big Data may be offset by challenges that threaten to widen health disparities. Moreover, persons with a more disadvantaged status are particularly vulnerable to unintended adverse effects of information system transformations.…”
Section: Potential Challenges Of Using Big Data For Minority Health Amentioning
confidence: 99%
“…arthritis, vision impairment etc.). [45] However, the potential of technology for better communication and disease management is clear; [46] therefore, given the burden of chronic disease in the elderly, it is imperative to develop more user friendly interfaces to facilitate better use of HIT for this age group. We also found that minorities showed more interest in using HIT, particularly for general health tips and medication reminders.…”
Section: Discussionmentioning
confidence: 99%
“…Published research has addressed whether or not patients experienced trouble accessing a provider who would take their insurance, 16 patterns of e-cigarette use, 17,18 strategies to reduce prescription drug costs, 19 internet use for health information, 20 and problems paying medical bills. 21 In addition, the Early Release Program has provided the first federal survey estimates of the impact of the ACA on increases in health insurance coverage.…”
Section: Post-aca Policy-relevant Questionnaire Changesmentioning
confidence: 99%